Surfactant induced aggregation–disaggregation of photodynamic active chlorin e6 and its relevant interaction with DNA alkylating quinone in a biomimic micellar microenvironment. Issue 99 (24th September 2015) - Jadhao, Manojkumar; Ahirkar, Piyush; Kumar, Himank; Joshi, Ritika; Meitei, Oinam Romesh; Ghosh, Sujit Kumar
Abstract : Ce6 undergoes enormous aggregation in the PMC of different surfactants which subsequently disaggregated after CMC and shows dynamic interaction with alkylating quinone. Abstract : The present paper epitomizes the detailed physicochemical behaviour of photodynamic active chlorin e6 (Ce6) and its interaction with the DNA alkylating quinone; 2, 5-dichloro diaziridinyl-1, 4-benzoquinone (AZDCIQ) in different bio-mimicking micellar microenvironments using steady state absorption, fluorescence, time resolved fluorescence and fluorescence anisotropy studies. Dramatic modulation in the photophysics of Ce6 has been observed in two types of surfactant assemblies namely premicellar and postmicellar assemblies of cationic CTAB, anionic SDS and nonionic TX-100. In water at pH 7.4, Ce6 exists as monomeric (73%, 4.91 ns) and dimeric (27%, 2.49 ns) forms, but with increasing concentration of CTAB in the premicellar region, the absorption and emission intensity decreases significantly due to the formation of surfactant induced higher aggregates. Interestingly further addition of CTAB (at critical micellar concentration and above) leads to disaggregation of those higher aggregates into its subsequent monomeric and dimeric form. In the case of TX-100 and SDS, the dye does not form higher aggregates in the premicellar region, rather it remains as monomeric–dimeric forms throughout the concentration range until the critical micellar concentration (CMC). After micellization, the percentage of Ce6 monomer increases in the case of TX-100, whereas the reverse case is observed in SDS, which may be explained by the forced dimerisation caused by repulsive interactions between anionic Ce6 and SDS micelles. The copper induced fluorescence quenching, solvation dynamics, and fluorescence anisotropy shows that the dye is localised in the Stern layer of CTAB, in the palisade layer of TX-100 and in the outer Gouy–Chapman layer or in aqueous bulk phase in the case of SDS micelles. The interaction of fully micellized PDT active Ce6 with DNA alkylating AZDCIQ is found to be more in CTAB as compared to TX-100 and water. The solvation dynamics of Ce6 in the presence of the quinone reveals the dynamic nature of the interaction between these two partners. The spectroscopic research described herein may provide numerous effective information for the use of chlorin(s) and alkylating quinones together to overcome the limitation of PDT, especially in the hypoxic environment of solid tumors.